ANALISIS HUBUNGAN JUMLAH PENDUDUK DAN KEPADATAN PENDUDUK DENGAN BAHAN BAKAR MINYAK TRANSPORTASI KOTA - Mudjiastuti Handajani; Bambang Riyanto (TATALOKA, 2013)
Fuel oil and transport is important to study because it relates to the environment and the local economy, nationally and globally. Fuel  for urban transport is influenced by the number and density of population. The purpose of the study is to analyze the population density of the city and fuel consumption/capita for metropolitan cities in the world, in Indonesia, the metropolitan city of Semarang and large city of Surakarta. The analysis is performed using bivarate. Metropolis developed countries shows: the more densely populated cities, fuel consumption/capita is the lower. For Indonesian cities and metropolitan cities of Semarang and Surakarta big show: the more densely populated city, fuel consumption does not always decreased. To be efficient fuel consumption city, the city's transportation system using mass public transportation and land use arrangements made compact. Efficient fuel consumption, can improve the health and economy of the State.